2012
DOI: 10.1074/jbc.m112.354001
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G Inhibits MicroRNA-mediated Repression of Translation by Interfering with the Interaction between Argonaute-2 and MOV10

Abstract: Background: APOBEC3G (A3G), which is part of cytidine deaminase family, significantly inhibits miRNA-mediated repression of translation, but the mechanism remains unknown. Results: A3G competitively binds to the C terminus of MOV10 to inhibit the interaction between AGO2 and MOV10. Conclusion: A3G affects the normal assembly or maturation of miRISC. Significance: Our data demonstrate a novel mechanism of the regulation of miRISC activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
61
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 44 publications
4
61
0
1
Order By: Relevance
“…Steps are numbered in small circles. Review against L1 mobilization include the RNA helicase MOV10 (which degrades L1 mRNAs or suppresses their translation) 24 and APOBEC3 family members (Figure 1b). 25 Different members of the APOBEC3 family may inhibit L1 retrotransposition by different mechanisms.…”
Section: Structure and Retrotransposition Process Of L1mentioning
confidence: 99%
See 1 more Smart Citation
“…Steps are numbered in small circles. Review against L1 mobilization include the RNA helicase MOV10 (which degrades L1 mRNAs or suppresses their translation) 24 and APOBEC3 family members (Figure 1b). 25 Different members of the APOBEC3 family may inhibit L1 retrotransposition by different mechanisms.…”
Section: Structure and Retrotransposition Process Of L1mentioning
confidence: 99%
“…miRNAs and lncRNAs may regulate gene expression directly or indirectly through competing endogenous RNA (ceRNA) networks. 68 In normal somatic cells, L1 retrotransposition is suppressed 22,31 and L1 transcripts are degraded or processed into regulatory RNAs that maintain cell homeostasis, 19,21,24,66,67 whereas in cancer, one study found that L1 transcripts were potentially biased toward cDNA formation and retrotransposition, 69 leading to speculation that deregulated regulatory RNA networks may drive tumorigenesis.…”
Section: Functions Of L1s In Cancer Retrotransposition-dependent Funcmentioning
confidence: 99%
“…The sequences of MOV10-specific small interfering RNAs (siRNAs) (SMARTpool) were described previously (31). MOV10-specific siRNAs and control siRNA were synthesized by Ribobio (Guangzhou, China).…”
mentioning
confidence: 99%
“…The cells were placed into 60-mm plates and further transfected with MOV10-HA-and NP-FLAG-expressing plasmids. Procedures were followed as previously described (31).…”
mentioning
confidence: 99%
See 1 more Smart Citation